A Multimodal Facial Emotion Recognition Framework through the Fusion of Speech with Visible and Infrared Images - Mohammad Faridul Haque Siddiqui (Multimodal Technologies and Interaction, 2020)
The exigency of emotion recognition is pushing the envelope for meticulous strategies of discerning actual emotions through the use of superior multimodal techniques. This work presents a multimodal automatic emotion recognition (AER) framework capable of differentiating between expressed emotions with high accuracy. The contribution involves implementing an ensemble-based approach for the AER through the fusion of visible images and infrared (IR) images with speech. The framework is implemented in two layers, where the first layer detects emotions using single modalities while the second layer combines the modalities and classifies emotions. Convolutional Neural Networks (CNN) have been used for feature extraction and classification. A hybrid fusion approach comprising early (feature-level) and late (decision-level) fusion, was applied to combine the features and the decisions at different stages. The output of the CNN trained with voice samples of the RAVDESS database was combined with the image classifier’s output using decision-level fusion to obtain the final decision. An accuracy of 86.36% and similar recall (0.86), precision (0.88), and f-measure (0.87) scores were obtained. A comparison with contemporary work endorsed the competitiveness of the framework with the rationale for exclusivity in attaining this accuracy in wild backgrounds and light-invariant conditions.